Factors Influencing Students’ Interest in Mathematics - Agosto Olo Tomé (International Journal of Research in Mathematics Education, 2025)
This study offers a fresh perspective on the perceptions of junior high school students toward mathematics learning in Timor-Leste, focusing specifically on seventh-grade students at Ensino Básico 3º Ciclo Santo António de Oe-Cusse. The research directly explores students’ learning experiences from their own viewpoint, which has rarely been documented in the educational context of the Oe-Cusse region. A descriptive qualitative approach was employed to understand the factors shaping students’ interest in mathematics. Eight students were purposively selected and asked to respond to the open-ended question: “What do you like about math lessons?” The findings reveal four main factors contributing to students’ enjoyment of mathematics: (1) clear teacher explanations that make the material easier to understand, (2) enjoyment of calculation activities such as addition, subtraction, and geometry, (3) the presence of games or puzzles that challenge concentration and creativity, and (4) awareness of mathematics’ relevance to daily life. These results indicate that students’ motivation to learn mathematics in this region is influenced by a unique combination of pedagogical, cognitive, and contextual factors, highlighting the importance of instructional approaches that integrate clear explanations, varied calculation activities, playful or puzzle-based elements, and real-world applications. This study provides valuable insights for developing mathematics teaching strategies that are tailored to the characteristics of students in Timor-Leste, particularly in border areas like Oe-Cusse, and opens avenues for further research on innovative teaching methods grounded in students’ perceptions and experiences.